«Treasure-human»: sacrality of the individual - Pysarenko, Yuriy (Actual Problems of Mind, 2017)
The paper deals with the development of some accounts on the sacrality of the individual in the history of culture. The authors employs the symbol «treasure-human» to refer to the highest implementation of the individual which is simultaneously a source of the collective and illustrates his point by example of «Skovoroda-Treasure» and «Treasure-Timon».